Perbandingan Rendemen Kelapa Sawit (Elaeis guineensis Jacq.) di Perkebunan Rakyat dan Perkebunan PT Tidar Kerinci Agung - Wulan Kumala Sari; Rusmanida Rusmanida (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2023)
Plantation of PT. Tidar Kerinci Agung (PT. TKA) is a company engaged in oil palm plantations with an area of 24,000 ha and has been certified by Indonesia Sustainable Palm Oil (ISPO). PT. TKA has a factory for Crude Palm Oil (CPO) processing, therefore the local community can sell their palm oil yield to the factory. However, the purchase of Fresh Fruit Bunches (FFB) from the community was constrained by the fact that many people use random seeds which reduce the quality of CPO, moreover the agronomic factors such as fertilization, rainfall, plant maintenance and harvesting on smallholder plantations which are the factors that can reduce the quality of CPO. The present study was conducted for 3 months, with the objective was to determine the comparison of the palm oil extraction rate between smallholder plantations and large-scale estate (PT. Tidar Kerinci Agung). The research method was a survey by purposive sampling to obtained data on oil palm production, especially in relation with oil extraction rate. The result showed that the oil extraction rate of CPO was 24.51% and it’s on Palm Kernel Oil (PKO) was 4.45% in large-scale estate (PT. TKA). It was higher than the oil extraction rate on smallholder plantations. The oil extraction rate of CPO and PKO in the high yielding, moderate yielding, and low-yielding smallholder plantations were CPO 20.55% and PKO 4.42%, CPO 21.50% and PKO 3.77%, and CPO 18.35% and PKO 4.34%, respectively.